2010
DOI: 10.1007/s11270-010-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Heavy Metals in an Urban Natural Wetland: The Nyabugogo Swamp (Rwanda)

Abstract: The Nyabugogo natural wetland (Kigali City, Rwanda) receives all kinds of untreated wastewaters, including those from industrial areas. This study monitored heavy metal concentrations (Cd, Cr, Cu, Pb, and Zn) in all environmental compartments of the swamp: water and sediment, the dominant plant species Cyperus papyrus, and fish (Clarias sp. and Oreochromis sp.) and Oligochaetes. Cr, Cu, and Zn concentrations in the water were generally below the WHO (2008) drinking water standards, whereas Cd and Pb were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Bioaccumulation of Cu by plant roots was higher at sites with water pH [ 8, as it was reported that at higher pH ([8.0) the presence of plaque enhanced Cu uptake into roots (Weis and Weis 2004). Similar results were also shown for Cu accumulation by Cyperus papyrus plant growing in an urban natural wetland of Rwanda (Sekomo et al 2011). J. repens and P. stratiotes shoots accumulated the most Cr (8.53 and 7.33 lg g -1 ) at Hanuman Setu and Pipraghat, respectively during the monsoon period.…”
Section: Resultssupporting
confidence: 80%
“…Bioaccumulation of Cu by plant roots was higher at sites with water pH [ 8, as it was reported that at higher pH ([8.0) the presence of plaque enhanced Cu uptake into roots (Weis and Weis 2004). Similar results were also shown for Cu accumulation by Cyperus papyrus plant growing in an urban natural wetland of Rwanda (Sekomo et al 2011). J. repens and P. stratiotes shoots accumulated the most Cr (8.53 and 7.33 lg g -1 ) at Hanuman Setu and Pipraghat, respectively during the monsoon period.…”
Section: Resultssupporting
confidence: 80%
“…Therefore even if plant uptake contributed to dissolved metals removal, it is likely not responsible for the noticed improved outlet EMCs. Several other researchers have identified that plant uptake wasn't a dominant process responsible for metal removal in wetlands or FTWs (Murray-Gulde et al, 2005;Kadlec and Wallace, 2009;Sekomo et al, 2011;Tanner and Headley, 2011).…”
Section: Plantsmentioning
confidence: 99%
“…The nug/sill ratios are often used for spatial heterogeneity and reflect the influence of regional factors (nature) and the role of non-regional factors (human factors). Soil is generally contaminated by heavy metals from two main sources: natural factors such as weathering, erosion of parent rocks, atmospheric deposition and volcanic activities; and anthropogenic activities such as sewage irrigation, addition of manures, fertilizers, and pesticides [24][25][26][27]. When C 0 / (C 0 +C) < 0.25, the variable space mutation gave priority to the structural variation (nature), and the variables have a strong spatial correlation.…”
Section: Data Processingmentioning
confidence: 99%